The coach-scientist relationship in high-performance sport: Biomechanics and sprint coaches - Waters, A.; Phillips, E.; Panchuk, D.; Dawson, A. (International Journal of Sports Science & Coaching, 2019)
It is common for sport science practitioners, including sport biomechanists, to interact with high-performance coaches in the daily training environment. These relationships are beneficial for both scientist and coach, as well as the athletes. However, as indicated by difficulties in transferring new research into coaching practice, these relationships are not functioning as well as they could. The aim of this paper is to examine the various factors that influence the coach-biomechanist relationship in the elite sprinting context and gain an understanding of what impedes and enhances this, which will ultimately maximise an athlete's performance. Sprint coaches (n = 56) and applied sport biomechanists (n = 12) were surveyed to determine the participants' experiences working with each other and use of biomechanics in the training environment. Semi-structured interviews with coaches (n = 8) and biomechanists (n = 8) were conducted to further explore these ideas. From the biomechanists perspective, the relationship appeared to be less effective than from the coaches' perspective and both groups identified areas for improvement. The coaches had an inconsistent understanding of biomechanics theory and the support a biomechanist could provide in the training environment, while it was acknowledged that biomechanists needed to improve their communication skills. Coach and practitioner education were identified as where these improvements could be facilitated. There are many aspects of the coach-biomechanist relationship that could contribute to establishing optimal practice in the high-performance environment and enhance the transfer of knowledge from scientist to coach. This paper proposes a number of directions that could be taken.